The day of the Jackal. Season one [videorecording (DVD)] - Bennett, Ronan (Universal Studios, 2025)
"Based on Frederick Forsyth's acclaimed novel, The Day of The Jackal follows an elite assassin known as 'The Jackal' as he works towards carrying out a seemingly impossible hit. However, his actions soon attract the attention of a British intelligence officer, Bianca, who sets out to hunt him down before his next kill. Armed with an array of disguises, skills, and weapons, we meet the Jackal carrying out his latest hit in Germany. Impressed by his work, an anonymous client reaches out with a proposal--the Jackal's riskiest job yet, but with a payout that may let him leave the game for good. The Day of The Jackal is a twisting, high-octane thriller about two highly skilled operatives engaging in espionage, subterfuge, and violence, as they stop at nothing to achieve their goals."--